Assessment of self-treatment in terms of inappropriate prescribing registry - S. Yu. Martsevich; V. V. Tsaregorodtseva; N. P. Kutishenko; Yu. V. Lukina; A. V. Zagrebelnyi; I. V. Mihailova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the frequency and characteristics of self-medication in patients with cardiovascular diseases within the Chuvashia Inappropriate Prescribing Study (CHIP) Registry.   Material and methods. The CHIP study is a cross- sectional study, which consistently included patients over the age of 50 who applied to a cardiologist at the outpatient clinic of the Republican Cardiological Dispensary. Exclusion criteria: presence of mental illnesses, oncological diseases detected less than 5 years ago, acute cardiovascular disorders within 6 months prior to treatment. The patient recruitment period is from 12/14/2023 to 08/07/2024. The physician conducted an examination, assessed drug therapy, adherence to it, and adjusted therapy in accordance with the clinical recommendations in force at the time of the study. The patients completed original adherence assessment questionnaires (the National Society for Evidence-based Pharmacotherapy Adherence Scale) and the pharmacotherapy features. This paper describes the research protocol and analyzes the data related to self-medication.   Results. The study included 300 patients (120 men and 180 women), 120 (40 %) of them had self-medication. 140 types of medicines were included in the number of medicines taken by patients on their own. Since some of the patients took more than 1 drug, 164 cases of self-medication were identified. The following types of self-medication were identified: self-administration of an unspecified drug (38.4 %), self-administration of a contraindicated drug (0.6 %), self-administration of an indicated drug but not prescribed by a doctor (2.4%), duplication of drugs belonging to the same class (3.6 %), replacement of the prescribed drug with an analog (5.5 %), justified self-medication (use of both over-the-counter and prescription drugs; 23.2 %), independent symptomatic use of over-the-counter drugs, which is not justified (26.3 %). When evaluating the results of self-medication, 7 (4.3 %) cases were identified when it led to the creation of a potentially dangerous combination of drugs. When duplicating drugs in 2 (1.2 %) cases, their combination was irrational. The replacement of the drug in 4 (2.4 %) cases was nonequivalent. There were no statistically significant differences between patients in the groups with and without self-medication, except for the presence of a history of acute cerebrovascular accident: among these patients, there were significantly fewer of those who took medications on their own.   Conclusion. In the CHIP registry, 40% of patients observed by a physician for cardiovascular diseases independently took drugs (both over-the-counter and prescription) together with or instead of the therapy prescribed by their physicians. Self-administration of an unspecified drug was the most common type of self-medication in CHIP register patients (38.4 %). In 4 % of cases, potentially dangerous drug combinations were the consequence of self-medication.